2010
DOI: 10.1021/ja909744z
|View full text |Cite
|
Sign up to set email alerts
|

Protonated [4n]π and [4n+2]π Octaphyrins Choose Their Möbius/Hückel Aromatic Topology

Abstract: Protonation-triggered conformational changes of meso-octakis(pentafluorophenyl) [36]octaphyrin and [38]octaphyrin have been investigated. The X-ray crystal structures and (1)H NMR analyses revealed that the protonation process cuts off intramolecular hydrogen bonds between aminic and iminic pyrrole units and, at the same time, produces intermolecular hydrogen-bond network between aminic pyrrole unit and counter-anions. Such a replacement induces some pyrrole inversion, leading to Mobius aromatic conformation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
149
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(161 citation statements)
references
References 51 publications
9
149
0
3
Order By: Relevance
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
See 2 more Smart Citations
“…[24] In subsequent reports it was shown that the ability to stabilize Möbius structures is a more general feature of porphyrinoids, and that the topology adopted by the macrocycle can be controlled to some extent. [25,26,103,110,[120][121][122][123][132][133][134] While the occurrences of Möbius aromaticity are still relatively rare, they are more frequent than could be expected. In fact, as we will discuss in more depth later, certain instances of Möbius topology (not always coinciding with well-defined aromatic character) were published in earlier porphyrinoid literature and remained unrecognized until recently.…”
Section: Möbius Aromaticitymentioning
confidence: 98%
“…[134] The unusual conformation, containing five inverted pyrrole rings, is stabilized in the solid state by an extensive network of hydrogen bonds between the NH protons of the macrocycle, counteranions and solvating molecules of acid, alcohol and water. The structure is apparently fluxional in solution but it was nevertheless characterized as aromatic.…”
Section: T1 and T2 Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] Später wurde gezeigt, dass die Fähigkeit zur Stabilisierung von Möbius-Strukturen eine allgemeine Eigenschaft der Porphyrinoide ist und die Topologie des Makrocyclus zu einem gewissen Maß kontrolliert werden kann. [25,26,103,110,[120][121][122][123][132][133][134] Möbius-Aromatizität kommt zwar relativ selten vor, aber dennoch weit häufiger, als man zunächst erwarten könnte. Weiter unten werden wir auf bestimmte Beispiele zur Möbius-Topologie, die eigentlich schon lange Bestandteil der Porphyrinoid-Literatur sind, aber bis vor kurzem nicht als solche erkannt worden waren, näher eingehen.…”
Section: Möbius-aromatizitätunclassified
“…[1][2][3][4][5][6] A principal aspect derived from structures of these compounds is aromaticity of central core and applicability of Hückel's rule to describe its electronic structure. [7][8][9] Among expanded compounds, Mc's of ABABAB-type (hemihexaphyrazine, H 3 Hhp) containing six consecutively interlinked 1,3,4-thiadiazole (A) and isoindole (B) subunits bridged by nitrogen atoms [10,11] induce a particular interest. Indeed, various substituted macroheterocyclic compounds of this type were synthesized to date [12][13][14][15][16][17][18] and their structures were confirmed by gas electron diffraction (GED) [19,20] and single crystal X-ray diffraction [21] methods.…”
Section: Introductionmentioning
confidence: 99%